Study of the effect of the ultrasonic pretreatment on the hydrothermal liquefaction of microalgae - Moure Abelenda, Alejandro (Cranfield University, 2016)
The depletion of the reserves of fossil fuel promotes the search for sustainable renewable sources of energy. Due to their similarities with the petroleum products, the biofuels represent a better alternative than other clean energies. The conversion process greatly depends on the biomass composition, which is a topic of debate, especially when it increases the price of the food. Therefore, third generation biofuels, derived from algae, are better accepted by society than using other raw materials. Due to the way of cultivating and the high moisture content of microalgae, hydrothermal liquefaction (HTL) is the transformation technology most suitable for this type of feedstock. Even when the application of HTL to microalgae is quite recent, a lot of research is being done because of the good expectations for biofuel production. In this way, the best operating conditions have already been determined, they are the critical point of water (374 ˚C and 221 bar), and the research is focussing now in the improvement of the quality of the products and the upscaling to a continuous process. The most important product is the biocrude, which has a high content of oxygen and nitrogen. The use of hydrogen for the removal of these heteroatoms is one of the most investigated techniques. Especially important is the presence of nitrogen, as the large production of NOx upon combustion is banned. The use of ultrasound as a pretreatment technology before the HTL of the microalgae slurry is intended to increase the yield of the biocrude while reducing the severity of the operating conditions. Also, milder conditions result in lower nitrogen content of the biocrude. This thesis shows the results of the use of a sonication bath to disrupt the microalgae cells before being liquefied. Three different microalgae species were considered: Nannochloropsis gaditana (N. gad.), Scenedesmus almeriensis (S. alm.), and Tetraselmis suecica (T. suec.). The experiments were carried out in a tubular batch reactor without stirrer and with an electric heater. It was found that the ultrasonic pretreatment does not affect the performance of the HTL of microalgae. The lack of influence of the pretreatment on the quantity and quality of the liquefaction products could be related to the fact that the microalgae samples were already disrupted during the drying process to prepare the powder biomass. Moreover, the poor performance of the sonication bath, in terms of achieving the microalgae cell breakage, is also considered as explanation. Therefore, the analysis of the ultrasonic equipment was done to understand the reason for its poor operation. The characteristics of the sonication equipment (configuration, ultrasonic power output, and energy frequency) were defined for future experiments.
Keywords: Sonication bath; liquefaction; biocrude; Nannochloropsis; Scendesmus; Tetraselmis